2012
DOI: 10.1186/1472-6882-12-146
|View full text |Cite
|
Sign up to set email alerts
|

Utilization pattern of traditional Chinese medicine for liver cancer patients in Taiwan

Abstract: BackgroundTraditional Chinese Medicine (TCM) is one of the most popular complementary and alternative medicine modalities worldwide. In Chinese and East Asian societies, TCM plays an active role in the modern health care system and is even covered by the National Health Insurance Program of Taiwan. Liver cancer is the second most common cancer in Taiwan. This study aimed to analyze the TCM utilization patterns of patients with liver cancer from 1996–2007 using a population-based random sample of one million in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 29 publications
4
33
0
Order By: Relevance
“…In our study, significant factors for TCM use included predisposing factors of gender and health beliefs, such as TCM use one year prior to leukemia diagnosis. Enabling factors observed were height of medical insurance, residential area, and urbanization level, which were similar to those reported by Liao et al [21, 22]. On the other hand, a particularly higher prevalence of TCM utilization was observed in central Taiwan, which has the highest per capita ratio of TCM physicians.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, significant factors for TCM use included predisposing factors of gender and health beliefs, such as TCM use one year prior to leukemia diagnosis. Enabling factors observed were height of medical insurance, residential area, and urbanization level, which were similar to those reported by Liao et al [21, 22]. On the other hand, a particularly higher prevalence of TCM utilization was observed in central Taiwan, which has the highest per capita ratio of TCM physicians.…”
Section: Discussionsupporting
confidence: 87%
“…A previous cross-sectional study investigated the medical visit patterns, characteristics, and prevalence of outpatient cirrhotic patients using TCM, and the amounts paid by the National Health Insurance for biomedicines and TCM in Taiwan [19]. It showed that on average, 19.5% of cirrhotic patients with HCC visited outpatient TCM clinics.…”
Section: Discussionmentioning
confidence: 99%
“…All of these significantly indicated the success of our HCC model. In recent years, many traditional Chinese drugs have been used for liver diseases and exhibit good effects in controlling liver cancer (Cheung et al, Effect of TGP on Rat HCC 2013; Liao et al, 2012). TGP is an effective composition extracted from the root of Paeonia Lactiflora.…”
Section: Discussionmentioning
confidence: 99%